Aksesibilitas Dalam Penyediaan Fasilitas Pelayanan SIM D Bagi Penyandang Disabilitas Di Satpas Colombo Kota Surabaya - Fadilla, Amara Ayu; Widiyantari, Cahya Fitri; Tukiman, Tukiman (Jurnal Ilmu Administrasi Negara (JUAN), 2021)
This study aims to determine the form of SATPAS Colombo responsibility in providing excellent service to guarantee accessibility for persons with disabilities in accordance with statutory regulations and accessibility to public service facilities for persons with disabilities. Accessibility is an convenience provided for all people, including persons with disabilities and the elderly in order to realize equal opportunities in all aspects of life and livelihood (Minister of Public Works Regulation No. 30 / PRT / M / 2006, 2006). This research uses descriptive qualitative research procedures, information collection is carried out using purposive sampling method and by means of observation, documentation, and interviews. SATPAS Colombo Kota Surabaya already has various facilities for people with disabilities. Infrastructure such as the provision of infrastructure facilities for public service applications for SIM D management, special parking for people with disabilities, special toilets, special waiting rooms, but not all of them meet the accessibility for persons with disabilities. Meanwhile, people with disabilities are also people who have the right to have easy access to public services, just like any other community. The results of this study are that several adequate facilities and infrastructure for persons with disabilities have been fulfilled, but still require special officers to serve persons with disabilities so that services can be carried out more optimally.